Let's say I have a grand partition function with two states $\epsilon_1$ and $\epsilon_2$:

\begin{equation} Z = \sum\limits_i \exp\left[-\beta\left(\epsilon_1 n_1+\epsilon_2 n_2 - \mu n_i\right)\right], \end{equation} where $n_1+n_2 = n_i$. Better formulation is in the comment of @By Symmetry.

I am interested in obtaining the average $n_1$.


I can rewrite my partition function as: \begin{equation} Z = \sum\limits_i \exp\left[-\beta\left(\epsilon_1 n_{1i}+\epsilon_2 \delta^{-1} n_{1i} - \mu (1+\delta^{-1}) n_{1i}\right)\right], \end{equation} where I used $\delta = n_1/n_2$.

If I take partial derivative over $\mu(1+\delta^{-1})$ this does NOT give me the average number of particles in the state $\epsilon_1$, because there is $\delta^{-1}$ in front of the $\epsilon_2$ term. Is there a way around it?

EDIT: $\delta$ is a bad variable as @Roger Vadim mentioned

  • 3
    $\begingroup$ I do not understand the first equation - what is $n_i$ here? Then it seems like you are summing over different values of $n_1$ and $n_2$, but treating their ratio, $\delta$, as if it were a constant. $\endgroup$
    – Roger V.
    Commented Jul 28, 2021 at 12:00
  • 2
    $\begingroup$ Am I correct in thinking the your first equation should be understood as $Z = \sum_\gamma \exp\left[-\beta(\epsilon_1 n_{1\gamma} + \epsilon_2 n_{2\gamma} - \mu (n_{1\gamma}+n_{2\gamma}))\right]$ where $n_{i\gamma}$ is the number of particles in energy state $i\in \{1,2\}$ in global system state $\gamma$? $\endgroup$ Commented Jul 28, 2021 at 14:21
  • $\begingroup$ @RogerVadim, thanks, there was a typo that I fixed and $\delta$ is not a good variable, see edit $\endgroup$ Commented Jul 28, 2021 at 17:06
  • $\begingroup$ @BySymmetry, this is much clearer way to formulate the problem, which is now mentioned in the question. Thank you! $\endgroup$ Commented Jul 28, 2021 at 17:07

1 Answer 1


Add the multiplicity to your equation, given $n = n_1 + n_2$:

\begin{align*} Z &= \sum_{n=0}\,\,\,\sum_{n1=0, n2=n-n1}^n \frac{n!}{n_1! n_2!} e^{-\beta\left\{\epsilon_1 n_1+\epsilon_2 n_2 - \mu (n_1+n_2)\right\}}.\\ &= \sum_n \,\sum_{n_1=0}^n \frac{n!}{n_1! n_2!} e^{-\left\{\beta\epsilon_1 \,n_1+\beta\epsilon_2\, n_2 - \beta\mu (n_1+n_2)\right\}}\\ &= \sum_n\,\sum_{n1, n2} \frac{n!}{n_1! n_2!} e^{-\left\{\beta (\epsilon_1 - \mu) \,n_1+\beta (\epsilon_2-\mu)\, n_2\right\}}\\ &= \sum_{n=0}^{\infty}\left\{ e^{-\beta (\epsilon_1 - \mu) } + e^{-\beta (\epsilon_2 - \mu) }\right\}^n = \sum_n z_1^n = \frac{1}{1-z_1} \end{align*} where $z_1 = e^{-\beta (\epsilon_1 - \mu) } + e^{-\beta (\epsilon_2 - \mu) }$, and $\ln Z = - \ln \left(1 - z_1 \right).$

The average number $\bar n_1$ \begin{align*} \bar n_1 &= \frac{1}{Z} \sum_n \, \sum_{n_1=0}^n n_1\,\frac{n!}{n_1! n_2!} e^{-\beta\left\{\epsilon_1 n_1+\epsilon_2 n_2 - \mu (n_1+n_2)\right\}}\\ &= \frac{-1}{Z}\frac{\partial}{\partial (\beta \epsilon_1)}\sum_n \, \sum_{n_1=0}^n \frac{n!}{n_1! n_2!} e^{-\beta\left\{\epsilon_1 n_1+\epsilon_2 n_2 - \mu (n_1+n_2)\right\}} \\ &= \frac{-1}{Z}\frac{\partial Z}{\partial (\beta \epsilon_1)} = -\frac{\partial \ln Z}{\partial (\beta \epsilon_1)}\\ &= + \frac{\partial}{\partial (\beta \epsilon_1)} \ln \left(1 - z_1 \right)\\ &= \frac{\partial}{\partial (\beta \epsilon_1)}\ln \left\{1- e^{-\beta (\epsilon_1 - \mu) } - e^{-\beta (\epsilon_2 - \mu) }\right\}\\ &= \frac{e^{-\beta (\epsilon_1 - \mu) } }{1 -e^{-\beta (\epsilon_1 - \mu) } - e^{-\beta (\epsilon_2 - \mu) } }\\ \end{align*}

  • $\begingroup$ My last version strayed into canonical ensemble. I had corrected to be in grand canonical. $\endgroup$
    – ytlu
    Commented Jul 28, 2021 at 23:38

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.